2022
DOI: 10.56933/pharmaspire.2022.14211
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements in nanoparticles drug delivery systems

Abstract: Nanoparticles in drug-delivery systems are generated by a variety of research survey. Unique physicochemical characteristics of nanostructured biomaterials include their very small and structural adaptability, high surface area to mass ratio, high reactivity, and controlled size. It enables molecularly focused cancer treatment, targeted administration of early detection of cancer lesions, early detection of cancer lesions, imaging agents, and anticancer medications, identification of tumor molecular factors by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
1
3
0
2
Order By: Relevance
“…This appears to be contrary to findings from a mixed effects logistic regression modelling of predictors of presumptive malaria treatment in private drug outlets in a 2018 national survey, which suggested that supervisory visits only improved malaria treatment practices by 1% [ 17 ]. However, this study’s findings agree with a 2018 paper on rational drug use, which asserted that a proper regulatory framework, including monitoring of operations in a drug outlet, is critical for ensuring the appropriate use of medicines [ 37 ]. Similarly, these findings agree with an earlier national survey, which concluded that the quality of treatment in the private sector requires, among other things, proper regulation of outlets [ 35 ].…”
Section: Discussionsupporting
confidence: 86%
“…This appears to be contrary to findings from a mixed effects logistic regression modelling of predictors of presumptive malaria treatment in private drug outlets in a 2018 national survey, which suggested that supervisory visits only improved malaria treatment practices by 1% [ 17 ]. However, this study’s findings agree with a 2018 paper on rational drug use, which asserted that a proper regulatory framework, including monitoring of operations in a drug outlet, is critical for ensuring the appropriate use of medicines [ 37 ]. Similarly, these findings agree with an earlier national survey, which concluded that the quality of treatment in the private sector requires, among other things, proper regulation of outlets [ 35 ].…”
Section: Discussionsupporting
confidence: 86%
“…6 Dari definisi tersebut maka penggunaan obat rasional harus memenuhi kriteria berikut: kesesuaian dengan indikasi; pemilihan obat yang didasarkan manfaat, keamanan, kesesuaian dan harga; pasien tidak memiliki kontraindikasi dan menunjukkan efek samping minimal; pasien menerima informasi mengenai kondisi medis dan obat yang relevan, akurat, dan jelas; serta adanya evaluasi atau monitoring efek yang tidak diharapkan selama pengobatan. 7 Penggunaan obat yang tidak rasional sebagian besar disebabkan oleh penggunaan terlalu banyak obat oleh satu pasien (polifarmasi), ketidaksesuaian penggunaan antibiotik seringkali dalam dosis yang tidak tepat untuk kondisi infeksi nonbakteri, kegagalan peresepan sesuai dengan panduan klinis, penggunaan obat berlebihan dan swamedikasi yang tidak tepat tanpa pergi ke fasilitas atau tenaga kesehatan. 6 Penggunaan obat tidak rasional dapat berdampak pada tidak tercapainya keberhasilan terapi, meningkatkan resiko efek samping, meningkatkan resiko resistensi antibiotik serta pemborosan biaya.…”
Section: Abstrakunclassified
“…For example, a medication with a once-daily dosing schedule might be preferred over one with multiple doses to enhance patient compliance, especially in the elderly who are likely to forget and therefore miss some doses [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Once the goals are determined, a suitable treatment is chosen, which can be challenging due to the various available options [7]. Ideally, the final selection of medication should be made after conducting a comprehensive benefit–risk analysis, considering both the medical factors and the patient’s circumstances, including availability and cost [6,8,9]. Patient-related factors, such as physiological conditions (e.g., allergy, liver impairment), susceptibility to adverse effects, and concurrent drug therapy, may influence the medicine selection process by potentially leading to drug interactions [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation